2022
DOI: 10.1038/s41467-021-27844-x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture underlying prey-dependent performance in a microbial predator

Abstract: Natural selection should favour generalist predators that outperform specialists across all prey types. Two genetic solutions could explain why intraspecific variation in predatory performance is, nonetheless, widespread: mutations beneficial on one prey type are costly on another (antagonistic pleiotropy), or mutational effects are prey-specific, which weakens selection, allowing variation to persist (relaxed selection). To understand the relative importance of these alternatives, we characterised natural var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The transcriptome of D. discoideum was also found to be highly species-specific when tested on 3 species of bacteria: K. pneumoniae , B. subtlis , and Mycobacterium marinum (56). Another study found that mutations that affect the ability of D. discoideum to grow on different bacteria were highly prey-specific (57). This suggests that there are different mechanisms for hunting or processing these distantly related bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptome of D. discoideum was also found to be highly species-specific when tested on 3 species of bacteria: K. pneumoniae , B. subtlis , and Mycobacterium marinum (56). Another study found that mutations that affect the ability of D. discoideum to grow on different bacteria were highly prey-specific (57). This suggests that there are different mechanisms for hunting or processing these distantly related bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…These variable transcriptional responses suggest that there are different mechanisms for hunting or processing these distantly related bacteria. Another study found that mutations that affect the ability of D. discoideum to grow on different bacteria were highly prey-specific (35).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted September 30, 2022. ; https://doi.org/10.1101/2022.09.28.509995 doi: bioRxiv preprint Bürger 2000). In contrast, observation of predominantly positive cross-environment mutational correlations (Fry and Heinsohn 2002;Baer et al 2006;Latimer et al 2014) as well as direct characterisation of individual mutations under different environmental conditions (Ostrowski et al 2005;Sane et al 2018;Stewart et al 2022), suggest that mutations more frequently have conditionally neutral (i.e., affecting the trait in only one environment) or concordant (synergistic) cross-environment effects.…”
Section: Introductionmentioning
confidence: 96%
“…A shift in fitness effects among environments suggests mutations may typically have antagonistic pleiotropic effects (i.e., trade-off) across environments, being beneficial under some conditions, but deleterious under others, consistent with theories of local adaptation (Felsenstein 1976; Bürger 2000). In contrast, observation of predominantly positive cross-environment mutational correlations (Fry and Heinsohn 2002; Baer et al 2006; Latimer et al 2014) as well as direct characterisation of individual mutations under different environmental conditions (Ostrowski et al 2005; Sane et al 2018; Stewart et al 2022), suggest that mutations more frequently have conditionally neutral (i.e., affecting the trait in only one environment) or concordant (synergistic) cross-environment effects.…”
Section: Introductionmentioning
confidence: 97%